Drivers and characteristics of the Indo-western Pacific Ocean capacitor - Du, Yan; Chen, Zesheng; Xie, Shang-Ping; Zhang, Lianyi; Zhang, Ying; Cai, Yinan (Frontiers in Climate, 2022)
Coherently coupled ocean-atmosphere variability of the tropical Indo-Pacific Oceans gives rise to the predictability of Asian summer climate. Recent advances in Indo-western Pacific Ocean capacitor (IPOC) theory and the relationship with El Niño-Southern Oscillation (ENSO) are reviewed. The IPOC features tropical Indian Ocean (TIO) warming and an anomalous anticyclonic circulation over the western North Pacific (WNPAAC), the latter driving water vapor transport to East Asia and causing extreme events, e.g., heavy rainfalls from central China to Japan during the boreal summer. IPOC events often occur in post-ENSO summers, but the significant TIO warming could sustain the WNPAAC without a strong El Niño, forced instead by a strong antecedent positive Indian Ocean Dipole (IOD). In latter cases, the Indian Ocean and WNP act as a self-sustaining system, independent of external forcings. El Niño or positive IOD induces the oceanic downwelling Rossby waves and thermocline warming in the southwest TIO, leading to SST warming and a “C-shaped” wind anomaly during winter and early spring. Furthermore, the southwest TIO downwelling Rossby waves reflect as oceanic Kelvin waves on the African coast. In the early summer, the resultant southeast TIO SST warming induces a second “C-shaped” wind anomaly. Both southwest and southeast TIO warming contribute to the WNPAAC. The WNPAAC modulates the water vapor pathways to East Asia in the late spring and summer, which mostly converge over the South China Sea and adjacent regions before flowing further to the north. More water vapor is transported from the western Pacific warm pool and less from the southern hemisphere and the Indian Ocean. The enhanced Asian Summer monsoon and moisture content lead to extreme rainfalls in central China and Japan during the boreal summer.